CAPTURE ALS: the comprehensive analysis platform to understand, remedy and eliminate ALS. Issue 1 (2nd January 2023) - Picher-Martel, Vincent; Magnussen, Claire; Blais, Mathieu; Bubela, Tania; Das, Samir; Dionne, Annie; Evans, Alan C.; Genge, Angela; Greiner, Russell; Iturria-Medina, Yasser; Johnston, Wendy; Jones, Kelvin; et al.
Abstract: The absence of disease modifying treatments for amyotrophic lateral sclerosis (ALS) is in large part a consequence of its complexity and heterogeneity. Deep clinical and biological phenotyping of people living with ALS would assist in the development of effective treatments and target specific biomarkers to monitor disease progression and inform on treatment efficacy. The objective of this paper is to present the Comprehensive Analysis Platform To Understand Remedy and Eliminate ALS (CAPTURE ALS), an open and translational platform for the scientific community currently in development. CAPTURE ALS is a Canadian-based platform designed to include participants' voices in its development and through execution. Standardized methods will be used to longitudinally characterize ALS patients and healthy controls through deep clinical phenotyping, neuroimaging, neurocognitive and speech assessments, genotyping and multisource biospecimen collection. This effort plugs into complementary Canadian and international initiatives to share common resources. Here, we describe in detail the infrastructure, operating procedures, and long-term vision of CAPTURE ALS to facilitate and accelerate translational ALS research in Canada and beyond.